Under My Wings My Life as an Impresario - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 2002)
Review of Paul Szilard, Alvin Ailey's impresario, recalls his career His autobiography, Under My Wings. PALABRAS CLAVE: Paul Szilard, autobiography, Alvin Ailey.
Under My Wings: My Life as an Impresario. Paul Szilard as told to Howard Kaplan, Limelight Editions.